Potential of Lazarevac municipal as framework of tourism development - Jovanović, Tatjana (Economics of Agriculture, 2010)
Lazarevac Municipal disposes of signifcant resources which could have decisive role in tourism development. During work on the paper, beside offcial statistical data of Statistical offce of the Republic of Serbia also was use available data of the Municipal.Results of this research shown that Lazarevac Municipal with its all settlements has a great chance for signifcant tourism development.Aim of the paper was to point out potential of the Municipal, on the one side and tourism development on the other side. Natural values of Lazarevac enable development of tourism, frst of all recreational. Numerous water potentials (river Kolubara with new simplex lake, Stara and Nova Očaga, several artifcial and natural lakes and pools) are wealth of Lazarevac and well development base especially for recreational, fshery and rural tourism.žMentioned resources, comparative advantages and development programs also give chance for tourism development.